(untitled) (Swiss Medical Weekly, 2017)
Pulmonary hypertension associated with left-sided heart disease (PH-LHD) is the most common type of pulmonary hypertension. In patients with left-sided heart disease, the presence of pulmonary hypertension is typically a marker of more advanced disease, more severe symptoms, and worse prognosis. In contrast to pulmonary arterial hypertension, PH-LHD is characterised by an elevated pulmonary artery wedge pressure (postcapillary pulmonary hypertension) without or with an additional precapillary component (isolated postcapillary vs combined postcapillary and precapillary pulmonary hypertension). Transthoracic echocardiography is the primary noninvasive imaging tool to estimate the probability of pulmonary hypertension and to establish a working diagnosis on the mechanism of pulmonary hypertension. However, right heart catheterisation is always required if significant pulmonary hypertension is suspected and exact knowledge of the haemodynamic constellation is necessary. The haemodynamic constellation (mean pulmonary artery pressure, mean pulmonary artery wedge pressure, left ventricular end-diastolic pressure) in combination with clinical information and imaging findings (mainly echocardiography, coronary angiography and cardiac magnetic resonance imaging) will usually allow the exact mechanism underlying PH-LHD to be defined, which is a prerequisite for appropriate treatment. The general principle for the management of PH-LHD is to treat the underlying left-sided heart disease in an optimal manner using drugs and/or interventional or surgical therapy. There is currently no established indication for pulmonary arterial hypertension-specific therapies in PH-LHD, and specific therapies may even cause harm in patients with PH-LHD.